1.
а)
[tex]4(3a + 2b - 6c) = 12a + 8b - 24c[/tex]
б)
[tex] - 3( - x + 5y - 7z) = 3x - 15y + 21z[/tex]
2.
[tex]4a - 34b - 24a - 3b = - 20a - 37b[/tex]
[tex]2.9a - 12.7c - a + 2c = 1.9a - 10.7c[/tex]
3.
[tex]6 - 3(x + 1) - (9 - x) = 6 - 3x - 3 - 9 + x = - 2x - 6[/tex]
[tex]2(7.5 - x) - (4.3 - 3x) = 15 - 2x - 4.3 + 3x = x + 10.7[/tex]
4.
[tex]5a - 5b = 5(a - b)[/tex]
[tex]14xy + 21ax = 7x(2y + 3a)[/tex]
Ответ:
№1
a)4(3a+2b-6c)=12a+8b-24c
b)-3(-x+5y-7z)=3x-15y+21z
№2
a)4a-34b-24a-3b= -20a-37b
b)2,9a-12,7c-a+2c=1,9a-10,7c
№3
a)6-3(x+1)-(9-x)=6-3x-3-9+x= -6-2x
b)2(7,5-x)-(4,3-3x)=15-2x-4,3+3x=10,7+x
№4
a)5a-5b=5(a-b)
b)14xy+21ax=7x(2y+3a)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
1.
а)
[tex]4(3a + 2b - 6c) = 12a + 8b - 24c[/tex]
б)
[tex] - 3( - x + 5y - 7z) = 3x - 15y + 21z[/tex]
2.
а)
[tex]4a - 34b - 24a - 3b = - 20a - 37b[/tex]
б)
[tex]2.9a - 12.7c - a + 2c = 1.9a - 10.7c[/tex]
3.
а)
[tex]6 - 3(x + 1) - (9 - x) = 6 - 3x - 3 - 9 + x = - 2x - 6[/tex]
б)
[tex]2(7.5 - x) - (4.3 - 3x) = 15 - 2x - 4.3 + 3x = x + 10.7[/tex]
4.
а)
[tex]5a - 5b = 5(a - b)[/tex]
б)
[tex]14xy + 21ax = 7x(2y + 3a)[/tex]
Ответ:
№1
a)4(3a+2b-6c)=12a+8b-24c
b)-3(-x+5y-7z)=3x-15y+21z
№2
a)4a-34b-24a-3b= -20a-37b
b)2,9a-12,7c-a+2c=1,9a-10,7c
№3
a)6-3(x+1)-(9-x)=6-3x-3-9+x= -6-2x
b)2(7,5-x)-(4,3-3x)=15-2x-4,3+3x=10,7+x
№4
a)5a-5b=5(a-b)
b)14xy+21ax=7x(2y+3a)